Proximal Subclavian artery injury managed without performing median sternotomy: a case report - Zia Ur Rehman (Journal of the Pakistan Medical Association, 2021)
Subclavian artery runs from chest to upper arm and is in close proximity to many important structures in the limited space. Subclavian artery injuries are rare and tough to manage. It is challenging to achieve proximal arterial control which in most cases require median sternotomy with its associated morbidity. Iatrogenic injuries to subclavian artery can happen in a hostile operative field as with patients with large neck tumors. We present a 35-year-male who had right subclavian artery injury during neck dissection which was repaired successfully via supra-clavicular approach. Continuous...